EFFECT OF SiC ADDITION ON HYDROGEN DESORPTION PROPERTIES OF NANOCRYSTALLINE MgH2 SYNTESIZED BY MECHANICAL ALLOYING - M. Maddah; M. Rajabi; S. M. Rabiee (Iranian Journal of Materials Science and Engineering, 2015)
In this study, the composite material with composition of MgH2-5 wt% SiC has been prepared by co-milling of MgH2 with SiC powder. The effect of milling time and additive on MgH2 structure, i.e. crystallite size, lattice strain, particle size and specific surface area, and also hydrogen desorption properties of obtained composite was evaluated by thermal analyzer method and compared with pure un-milled MgH2. The phase constituents and grain size of powder were characterized by X-ray diffractometry method. It has been shown that addition of 5 wt% SiC to MgH2 and mechanical alloying up to 30 h formed a nanocrystalline composite with the average crystallite size of 12 nm, average particle size of 0.5 µm and specific surface area of 10 m2/g. On the other hand, SiC can help to break up particles and reduce the particle size. As a consequence, the desorption temperature of composite material milled for 30 h has decreased from 435 °C to 361 °C.